Labor flexibilization and globalization: changes in traditional human resources management - Iftekhar Amin Chowdhury; Anna Rahman (Daffodil International University, 2007)
This paper analyzes how changes to the global organization of capitalism accompanied and intensified by globalization through HRM policies, which affect the regulation of labor and the employment relationship. One of the most significant of these changes has been the dramatic increase in the rate of cross-border merger and acquisition activity. Of equal significance, especially for the regulation of labor and the employment relationship has been the pronounced tendency of global enterprises to transform themselves into coordinators and organizers of activities performed for them by contractors, sub-contractors and suppliers. Outsourcing and subcontracting have allowed global enterprises to reduce and externalize the costs incurred from the direct employment of labor. The growing dominance of Human Resource Management (HRM) in the regulation of labor and the employment relationship has occurred in tandem with the increasing flexibilization of labor. Some aspects of this are exemplified through the increasing trend in part time labor and eradication of gender bias in the garments industry as well as part time employment and flexi time in the rapid emergence of private educational sectors in Bangladesh. In addition, some thoughts on the growing HR system in Bangladesh are discussed with emphasis on the main characteristics of its workforce.